ANALISIS PENGARUH PERUBAHAN SPREAD SUKU BUNGA TERHADAP KINERJA MAKROEKONOMI INDONESIA PERIODE 1993:I – 2005: II Pendekatan Jalur Kredit dan SVAR - Banoon Sasmitasiwi; Malik Cahyadin (Faculty of Economics and Business, Universitas Gadjah Mada, 2006)
This research is intended to analyze the influence of the change of interest rate spread to macroeconomic performance in Indonesia. The interest rate spread includes of Fed rate, Germany rate, and China rate. The realization of banking restructuring, which emphasized on program of credit restructuring as result from presence of currency crisis and banking crisis, is held with considered on condition of Indonesian’s macroeconomic. Finally, this research will effected on activity of real sector. In this research, macroeconomic condition is indicated by real Gross Domestic Product (GDP), real credit behavior, real exchange rate, and also real sector condition itself. The activity of real sector is showed by behavior of manufacturing sector and construction sector. The data employed in the study are secondary time series data from quarterly data for period of 1993:I-2005:II. They constitute observation consisting of 50 series of data of picked from several publication. The method of analysis used in the study are structural vector autoregression model with emphasized on impulse response analysis. The result of structural vector autoregression model, which be showed by impulse response analysis, suggests that Gross Domestic Product (GDP), credit behavior, and real sector give negatively response to positive shocks or Gross Domestic Product (GDP), credit behavior, and real sector decreased. This estimation result offer strong empirical evidence for effectiveness and relevance of a credit channel in Indonesia. Positive shocks are shocks to increases in interest rate spread. In this research, interest rate spread are spread between domestic lending rate and US interest rate, domestic lending rate and German interest rate, and domestic lending rate and China interest rate. Futhermore, the estimation result also show that shocks of an increase in interest rate spread caused real appreciation.